Patrick Douglas Baird, 1912-1984 - Orvig, Svenn (ARCTIC, 1984)
. It was in Baffin Island that Pat Baird first set foot in Canada. He was to return there many times, for he came to love the Arctic, its mountains, snow and ice. . Pat Baird became a well-known public figure in 1945-46, when he participated in the celebrated "Lemming" and "Muskox" military exercises in the Canadian northwest. Because of his experience, he led the main party in Exercise Muskox, an unprecedented automotive journey of 3400 miles around the Canadian Arctic, starting in Churchill and going to Victoria Island, then as far as Coppermine and back to the Peace River country. He did this successfully and well, and did not suffer any accidents or lose any men on his party. Col. Baird's decade of arctic and military experience led to his appointment as chief of the Arctic Section of the Canadian Defence Research Board. A year later, in 1947, he was made Director of the Montreal (head) Office of The Arctic Institute of North America, a post he held until his return to Scotland in 1954. During that time he planned and led two major expeditions to Baffin Island - to the Barnes Icecap region in 1950 and to the Pangnirtung Pass area and the Penny Highland in 1953. On these expeditions, glaciological investigations were undertaken for the first time in Canada's Arctic, and Pat became an authority on mountain glacier research and arctic mountaineering. . On his return to Canada in 1959 Pat Baird was appointed Director of the Gault Estate of McGill University . and Supervisor of Northern Field Studies in the Department of Geography [Schefferville Subarctic Research Station. After his retirement in 1969, Pat Baird continued to travel] . on several subsequent climbing trips to his beloved Baffin Island, where Baird Peninsula is named after him. .